Stakeholder diversity matters: employing the wisdom of crowds for data-poor fisheries assessments - Benjamin L. H. Jones; Rolando O. Santos; W. Ryan James; Samuel Shephard; Aaron J. Adams; Ross E. Boucek; Lucy Coals; Sophia V. Costa; Leanne C. Cullen-Unsworth; Jennifer S. Rehage (Scientific Reports)
Abstract Embracing local knowledge is vital to conserve and manage biodiversity, yet frameworks to do so are lacking. We need to understand which, and how many knowledge holders are needed to ensure that management recommendations arising from local knowledge are not skewed towards the most vocal individuals. Here, we apply a Wisdom of Crowds framework to a data-poor recreational catch-and-release fishery, where individuals interact with natural resources in different ways. We aimed to test whether estimates of fishing quality from diverse groups (multiple ages and years of experience), were better than estimates provided by homogenous groups and whether thresholds exist for the number of individuals needed to capture estimates. We found that diversity matters; by using random subsampling combined with saturation principles, we determine that targeting 31% of the survey sample size captured 75% of unique responses. Estimates from small diverse subsets of this size outperformed most estimates from homogenous groups; sufficiently diverse small crowds are just as effective as large crowds in estimating ecological state. We advocate for more diverse knowledge holders in local knowledge research and application.